Considering Ideational Meaning On The Speech Of Reporting Covid-19 News By Achmad Yurianto - Zulfahmi, Rezi (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
Ideational meaning is one of three functions of language. Ideational meaning is meaning about phenomena, about things (living and non living, abstract and concrete), about goings on (what the things are or do) and the circumstances surrounding these happenings and doings. The aims of this research are to identify the ideational meaning realized in speech of reporting Covid-19 news and to find out the most dominant process type found in speeech of reporting Covid-19 news. Descriptive qualitave method was applied. The data were collected from the speech of reporting Covid-19 news by Achmad Yurianto as the object of research. Data collection methods were used watching in youtube based on real situation. The activities in the data analysis was included data reduction, data display and data veritification. From 15 clauses which have been analyzed, Researcher find out six sequences of process. They are Material process (5) which presents the process of doing and happening, Relational process (3) which shows the process of being and having, Mental process (3) which reflects the process of thinking, feeling and perception,Verbal process (2) which involvest he process of saying or giving message through language, Behavioral process (0) which presents the process of behaving, and Existential process (2) which presents the process of existence. The most dominant process here is material process.